PESAN PESAN KOMUNIKASI ISLAM DALAM SYAIR SENANDUNG PADA KEBUDAYAAN MELAYU BATUBARA - Nur Hasanah (Al-Balagh : Jurnal Komunikasi Islam, 2017)
Abstract: This research are aim to knowing the message and communication principles of Islamand to analyze the communication aspect of Islam that contained in poetry humming at BatubaraMalay culture. The theory that used in this research are theory of designing messages proposedby Kenneth Burke about “language as a vehicle for behaviour” and malay oral literature theorythat is spontanity theory that proposed by Tuanku Luckman Sinar Basarshah on “theories thatfocus on the role of puppeteer as a lead media”In this research, researcher using Content Analysis (Analisis Isi) by using interview techniquewith some community members and traditional leaders who knows and understands in poetryhumming at Batubara Malay culture. That in poetry humming brandish moppet there is amessage islamic communication which is reflected in the sentence bismillah, fortunately, alms,fringe benefits the parents, and advice.Then theres Islamic communication principles that isprinciple Package (heart, spoken, act), Qaulan Baliqhan, Qaulan Karima which is reflected inthe sentence being enemy and disease become medicine. And islamic communication aspect thatcontained in poetry humming brandish moppet are aspects of education which is reflected in thesentence teach our children religious knowledge, so that children knowledgeable. Social aspectwhich is reflected in the sentence neighbour are the closest allies.